Hakikat Manusia dan Pendidikan dalam QS Al-‘Alaq Ayat 1-5 - Fellanika Destiani; Hana Fauziyah; Imroatus Soleha; Abdul Aziz (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
In this article, we discuss the nature of human beings as learning creatures and creatures who are always dependent on Allah SWT as contained in QS. Al-'Alaq verses 1-5. What is a special fact in this article is the urgency of understanding Islamic education in answering modern challenges through strengthening the values of monotheism and spirituality. The purpose of this study is to analyze in depth the meaning of education and human existence in the perspective of tarbawi interpretation of the early verses of surah al-'alaq. This research uses a qualitative approach with the type of library research. The data collection technique uses literature review by studying verses of the Qur'an. Data analysis was carried out in a descriptive-qualitative manner with an interpretative approach to the text and the thoughts of experts. The results of the study show that qs. al-'alaq 1-5 affirms that man was created as a learning creature who obtains knowledge from Allah and in the process of learning always needs His guidance. This article emphasizes that the theory of Islamic education must be based on the theory of education should be based on the principle of monotheism which combines intellectual intelligence and spiritual awareness.